1993
DOI: 10.1017/s0021932000020253
|View full text |Cite
|
Sign up to set email alerts
|

Do men grow to resemble their wives, or vice versa?

Abstract: Sixty-eight engaged couples, 113 newly weds, and 222 couples married for over 5 years, were studied for a number of physical, psychological and socioeconomic traits. The measurements were repeated a year later. Correlations were highest for age (r = 0-454, 0-903 and 0-888 respectively). They were also high for height (but not weight), neuroticism (but not extroversion), occupation, education, religion and smoking. Similarities were already present about the time of marriage, with little convergence or divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Second, our results do not suggest that marital correlations should be taken as a sign of common environmental influence unless investigators can demonstrate that these correlations are significantly greater than those due to assortment. This is consistent with data from a study questioning whether men and women grow to look like their spouses (Sutton, 1993). Sutton found that spouses do not grow to resemble one another.…”
Section: Discussionsupporting
confidence: 86%
“…Second, our results do not suggest that marital correlations should be taken as a sign of common environmental influence unless investigators can demonstrate that these correlations are significantly greater than those due to assortment. This is consistent with data from a study questioning whether men and women grow to look like their spouses (Sutton, 1993). Sutton found that spouses do not grow to resemble one another.…”
Section: Discussionsupporting
confidence: 86%
“…If one person smokes cigarettes in a relationship, it is not uncommon for the partner to also be a smoker (Sutton, 1993). In a study of smoking cessation, just over a third of the sample reported that their partners also smoked (Roski, Schmid, & Lando, 1996).…”
mentioning
confidence: 99%
“…In a study of similarity among newlyweds (Houts, Robins, & Huston, 1996), couples were found to be more similar on role preferences and leisure activities than one would expect by chance, thus providing some evidence for assortative mating. Sutton (1993) found that across a wide range of characteristics (e.g., age, education, religion, personality, etc) "...similarities between partners are already present at the outset [of marriage]" (page 28). Taken together, these findings suggest that, for some characteristics, assortative mating may explain spousal similarities.…”
mentioning
confidence: 99%
“…For this reason, we included only smoking-discordant couples in our study. Given that a recent study of BCT reported similar success rates when one or both partners had an AUD (Schumm, O’Farrell, & Andreas, 2012), that tobacco use is highly correlated within couples (Sutton, 1993), and that partner smoking is related to relapse (Kahn, Certain, & Whitaker, 2002), a BCT intervention for couples in which both partners smoke may be warranted. Future research should examine this question.…”
Section: Discussionmentioning
confidence: 99%